Evaluation of the expression and proliferation of degenerative markers in primary cell cultures obtained from human intervertebral disc tissue (Annals of Medical Research, 2021)
Aim: A major cause of low back pain is disc degeneration. Nevertheless, no specific and reliable markers of the degeneration of the nucleus pulposus (NP) are available. This presented study aimed to examine changes in the expressions of genes in primary cell cultures isolated from intact and degenerated tissues to give insights into the biopathogenesis of intervertebral disc (IVD) tissue.Material and Methods: Tissues of eight patients (n = 8; average age: 41.74 ± 9.86 years) were resected through microdiscectomy, and primary cell cultures were prepared using degenerated disc tissue. The cultured degenerated tissues served as the study group. The samples in the control group comprised the intact tissues of patients (n = 8; average age: 38.68 ± 7.91 years) resected following a trauma. Morphology of the cell surface were evaluated using an inverted light/fluorescent microscopy at 0 and 24 h on days 10 and 21. The expressions of the chondroadherin (CHAD), cartilage oligomeric matrix protein (COMP), interleukin-1 beta (IL-1 beta), and matrix metalloproteinase (MMP)-7 and MMP-19 genes were evaluated using the reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The data obtained were statistically analyzed.Results: The four genes investigated, except COMP (P > 0.05), changed significantly in primary cell cultures isolated from degenerative IVD tissues. This result was statistically significant (P 0.05). The gene expressions in the samples derived from intact IVD tissues changed markedly and these changes were associated with proliferation (P 0.05).Conclusion: Analyzing the changes in gene expression levels associated with IVD should contribute to future studies on the prevention and treatment of such pathologies. The data obtained from the present study will shed light on cellular-based personal targeted therapies through which genetic information can be transmitted to cells.
Keywords: CHAD; COMP; degenerative markers; IL-1β; intervertebral disc; MMP